Origine et expansion de l’Afro-Asiatique : méthodologie pour une approche pluridisciplinaire - M. Ben Hamed; Pierre Darlu (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Afro-Asiatic linguistic group occupies a geographical zone which straddles two continents, Africa and Asia, a distribution which brings into question the location of this family’s homeland. Linguistics, Population Genetics and Archaeology have tried unsuccessfully to provide an answer, because the specificity and the interpretative nature of their different approaches make the homeland issue even more complex, and calls for reconsideration of the methodology used. This paper is a methodological reflection on the development of a linguistic group and an attempt to define an overall theoretical framework to consider the development of human populations in syncretic, biological and cultural terms. We present here a critical review of the linguistic and extra-linguistic methods applied to the question of an Afro-Asiatic homeland. We propose a single methodology taking into account the limitations observed in past and current works on the subject, the considerations related to each discipline as well as the particular impacts due to the nature of the available data.